Frequency of anti-Toxoplasma gondii antibodies in dogs and cats from the metropolitan region of Vitória, Espírito Santo, Brazil - Covre, Kamila Cunha; Farias, Priscila Camargo Granadeiro; Müller, Rosângela Aparecida; Amorim, Vanessa Gobbi; Lopes, Rosalida Estevan Nazar; Salaroli, Luciane Bresciani; Vitor, Ricardo Wagner de Almeida; Fux, Blima (Archives of Veterinary Science, 2022)
Toxoplasmosis, an infection caused by Toxoplasma gondii, is widely distributed. Seroprevalence in pets is a reliable tool to determine environmental parasite presence and human risk of infection due to proximity to these animals. The frequency of anti-T. gondii IgG antibodies in sera of dogs and cats from Espírito Santo, Brazil and risk factors associated with the infection (sex, age, allocation, and breed) were assessed. Antibodies against T. gondii were detected in 39.4% (149/378) and 38.1% (142/373) of the dogs by enzyme-linked immunosorbent assay (ELISA) and by indirect immunofluorescence antibody test (IFAT), respectively. In cats, antibodies were detected in 15.2% (12/79) by ELISA and 7.6% (6/79) by IFAT. Canine infection was associated with stray origin and older ages. There was an agreement between techniques in the detection of antibodies in dogs (0.82) and cats ( 0.63). These results indicate the parasite presence in the urban environment, suggesting the possibility of infection to humans and other animals. However, this risk is lower considering pet domiciled animals with control diet and better hygiene conditions.